Strengthening Cyber Law in the Protection of Indonesian Migrant Workers: A Case Study of Online Scam Operations in Cambodia - Silviana Cindy Kharissa; Hurun Sajidah; Dede Kania (Universitas Negeri Gorontalo, 2025)
Digital technology has opened up many job opportunities around the world, including opportunities to work abroad. High salary offers are one of the factors driving Indonesians' interest in working abroad. However, this situation is often exploited by irresponsible parties to commit fraud using victims' information, which ultimately leads to human trafficking crimes. The number of online fraud victims among Indonesian migrant workers abroad increased from 15 cases in 2020 to 7,027 cases in 2025, with 4,300 cases occurring in Cambodia. This highlights the weakness of state protection for its citizens in the digital age. This paper focuses on analyzing the modus operandi of online scams targeting Indonesian migrant workers, the efforts undertaken by the Indonesian government, and the enforcement of laws in Cambodia against illegal activities. This research employs a normative legal and descriptive qualitative approach. From the discussion, it is known that the modus operandi of online scams targeting Indonesian citizens involves facilitating the recruitment process, forging data and documents, visa abuse and travel manipulation, as well as abuse of foreign legal jurisdiction. Efforts to address and prevent labor exploitation through online scams involve all levels, including international cooperation, the role of the government, and public awareness. Furthermore, the weakness of law enforcement and economic interests has created a dependency on illegal activities that not only threaten the internal stability of Cambodia but also harm Indonesia socially, economically, and legally.